Sarcopenia em idosos com diabetes assistidos em unidades de assistência à saúde : revisão de escopo - Lopes, Gabriella Farias (2024)
Sarcopenia is related to the insulin dysfunction in the elderly, and due to the natural deterioration of bone functions in the physiological process of senescence, Diabetes Mellitus emerges as a worsening factor. The objective of this study is to map evidence regarding sarcopenia in elderly diagnosed with diabetes who are assisted in health assistance units. This study is a scope review based on the assumptions elaborated by The Joanna Briggs Institute. The mnemonic "PCC", where "P" stands for Population (the elderly), "C" for Concept (sarcopenia and diabetes) and "C" for Context (health assistance units), was utilized and resulted in the following question: "What are the evidences regarding sarcopenia in the elderly with diabetes assisted in health assistance units?". The inclusion criteria considered: studies developed with elderly individuals and studies which described, evaluated and/or investigated diabetes and sarcopenia in the elderly. Were excluded the studies with individuals with less than 60 years of age as well as the elderly; duplicate articles; studies which involved institutionalized elderly or which did not clarify whether it was made in a health assistance unit; letters, editorials, reflection and review studies. Search occurred between November and December of 2023, in the following bases: Scopus, Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), MEDLINE via PubMed, EMBASE, Scientific Electronic Library Online (SCIELO), and Web of Science. Beyond that, were considered gray literature studies such as: Google Scholar, Catálogo de Teses e Dissertações da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), Biblioteca Digital Brasileira de Teses e Dissertações (BDTD) and Open Access Theses and Dissertations (OATD). The Rayyan software was used for selection of the studies by two reviewers, and, following that, the results were attached through Google Sheets. 31 studies were found that answered to the inclusion criteria, with the result synthesis and data discussion presented in a narrative manner, as well as with illustrative tables and a data processing and similitude analysis software. The study's results found 31 studies varying from 2016 to 2023, focused on America, Asia and Europe. Through said studies, it was possible to point out a myriad of clinical and biochemical factors that intertwine sarcopenia and diabetes in the elderly. This review brought new information for both sarcopenia and its' association to diabetes.However, more research is needed in order to further base and deepen the data found in this review.